2018
DOI: 10.1021/acs.energyfuels.8b02693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wax Inhibitor Performance through Various Techniques

Abstract: Various techniques were used to compare the effectiveness of a commercially available wax inhibitor (WIA) to a newly developed wax inhibitor (WIEP) using a highly waxy Wyoming crude oilwhich causes plugging within wellbores and pipelines. The two additives were compared using centrifuge experiments, cold finger tests, and the precipitation and redissolution waxphaltene determinator (WD) method. Centrifuge tube experiments, and cold finger tests, showed that the newly developed WIEP additive was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…100 However, very few studies have investigated the effect of chemical additives on the solubility curve. 101 Adams et al 101 reported that adding chemical additives inhibited the wax precipitation using centrifuge tests, which revealed that the Pour point is the temperature at which the crude oil starts losing its fluidity. Once the yield stress of the gel is high enough to exceed the pipeline pressure, then the pipeline cannot be operated.…”
Section: Testing Parameters: Assessment In Thementioning
confidence: 99%
See 3 more Smart Citations
“…100 However, very few studies have investigated the effect of chemical additives on the solubility curve. 101 Adams et al 101 reported that adding chemical additives inhibited the wax precipitation using centrifuge tests, which revealed that the Pour point is the temperature at which the crude oil starts losing its fluidity. Once the yield stress of the gel is high enough to exceed the pipeline pressure, then the pipeline cannot be operated.…”
Section: Testing Parameters: Assessment In Thementioning
confidence: 99%
“…Several techniques can be used to obtain it, such as DSC, filtration and centrifugation, pulsed NMR, FT-IR, and HTGC . However, very few studies have investigated the effect of chemical additives on the solubility curve . Adams et al reported that adding chemical additives inhibited the wax precipitation using centrifuge tests, which revealed that the inhibitor mechanism is not just simple “sequestering” effects.…”
Section: Testing Parameters: Assessment In the Laboratorymentioning
confidence: 99%
See 2 more Smart Citations
“…Perez et al 235 found that pour point depressants are often ineffective when the crude oils have high boiling points or high aromatic content or contain high content of wax molecules with nalkane carbon chains greater than 25, while they are effective when crude oils have high asphaltene content and high resin or total acid value or contain wax molecules with n-alkane carbon chains less than 25. Adams et al 236 developed an automated separation wax tester that can discriminate easily crystallizable wax fractions from crude oil, thus allowing preliminary and rapid identification of crude oil sensitivity to pour point depressants. Senra et al 27 found that C 32 was able to cocrystallize with C 36 but stearic acid did not cocrystallize with either C 32 or C 36 at any concentration.…”
Section: Chemical Strategiesmentioning
confidence: 99%